2018
DOI: 10.1186/s13104-018-3830-7
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital mortality of patients with cardiogenic shock after acute myocardial infarction; impact of early revascularization

Abstract: ObjectivesThe purpose of this study was to determine the frequency of in-hospital mortality in 351 patients who developed cardiogenic shock after acute myocardial infarction and by determining this; we might find that how efficiently we could manage this serious condition in our population by knowing the factors which are associated with high mortality after cardiogenic shock. Moreover impact of early revascularization like thrombolytic therapy or angioplasty was also evaluated.ResultsMean age was 65.41 ± 7.78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 27 publications
5
37
0
3
Order By: Relevance
“…Our finding was in agreement with a study done by Dziewierz et al, where patients with cardiogenic shock were 7.39 times more likely to die in-hospital (95% CI:4.50-12.11) [64]. Similar finding from Afghanistan claimed that, of 351 patients with cardiogenic shock, the in-hospital mortality was reported about 44.7% [62].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding was in agreement with a study done by Dziewierz et al, where patients with cardiogenic shock were 7.39 times more likely to die in-hospital (95% CI:4.50-12.11) [64]. Similar finding from Afghanistan claimed that, of 351 patients with cardiogenic shock, the in-hospital mortality was reported about 44.7% [62].…”
Section: Discussionsupporting
confidence: 93%
“…Patients with cardiogenic shock in ACS should be treated with reperfusion therapy; supportive fluids and ionotropic agents [61]. The above finding could be due to inadequate use of reperfusion therapy [62]. However, a retrospective study conducted in Oman reported that out of 63 ACS patients having cardiogenic shock, the in-hospital mortality was 52.4%, even though 93.6% of them underwent PCI [63].…”
Section: Discussionmentioning
confidence: 99%
“…Above cited studies emphasize the continuous use of Killip class in resource depleted setting like ours and still nd its utility in risk strati cation of patients with LVF secondary to MI. MI is associated with high mortality and multiple complications in our population [8,9]. As no such facilities (emergency angioplasty and emergency bypass surgery) are available in tertiary care hospitals, so mortality may be different in each class.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is more practical than the femoral approach; it is associated with a higher rate (5-10%) of asymptomatic radial artery occlusion [6]. In third world countries like Pakistan, complication rates of cardiovascular diseases are quite high [7][8][9][10] and there is need to utilize effective techniques that can reduce complication rates.…”
Section: Introductionmentioning
confidence: 99%